Factors that influence Australian early career nurse employment outcomes and settings: A prospective cohort study. (11th October 2020) - Cottle‐Quinn, Amanda; Tower, Marion; Eley, Rob
Abstract: Aim: To identify the factors influencing employment outcomes and settings for early career nurses. Background: A shortage of nurses attracted to work in out‐of‐hospital settings exists. Despite this, not all nursing graduates can secure work as a nurse. Information on the factors that impact wider graduate employment is available. However, a nursing perspective is missing, especially for hard to recruit to areas. Methods: A prospective cohort study was conducted. Participants were 293 final‐year undergraduate nursing students, recruited from two universities. Data were collected over 12 months, commencing November 2016. Results: English as a first language was the greatest predictor of employment for graduates. Previous health care experience and workplace preferences predicted employment in the out‐of‐hospital setting. Conclusions: Misalignment between English language requirements and industry expectations about language may lead to bias in recruitment of graduate nurses with English as their second language. Recruitment to out‐of‐hospital settings may be promoted by having health care experience and targeting those with a preference. Implications for Nursing Management: Reviewing current employment policies to ensure they reflect the need for cultural diversity in the nursing workforce is critical. Additionally, research that aims to understand how preferences for out‐of‐hospital settings are developed will help target graduate employment strategies.